Pengaruh Citra Destinasi, Fasilitas Wisata dan Experiental Purchasing terhadap Kepuasan Konsumen (Studi pada Pengunjung Domestik Heha Sky View Gunungkidul) - Yuseni, Finacatrin; Asteria, Beta (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to determine the effect of destination image, tourist facilities and experiental purchasing variables on customer satisfaction on Heha Sky View Gunungkidul tours, Yogyakarta. This type of research is descriptive research with a quantitative approach. This research data is primary data taken through a questionnaire to 100 respondents using purposive sampling technique, which is then analyzed using multiple linear regression and hypothesis test through SPSS 23 software. The result obtained show that destination image has a positive significant effect on customer satisfaction, tourist facilities have a insignificant effect on customer satisfaction and experiental purchasing have a positive significant effect on customer satisfaction.